Soft tissue infection of the head and neck in HIV -A vexing diagnostic conundrum - R Keerthi; Tulasi Nayak (Wolters Kluwer Medknow Publications, 2016)
Necrotizing soft tissue infections (NSTI) are a spectrum of aggressive and devastating conditions with a high mortality rate. Immunocompromised patients are highly susceptible to these infections and may manifest unusual variants and varied combinations of the various conditions in this spectrum. We present here an unusual case of NSTI of the head and neck in an HIV-positive patient, highlighting the difficulty in diagnosis and the importance of lab risk indicator for necrotizing fasciitis scoring and swift, aggressive surgical therapy.